The Importance Of Vocabulary In Reading Among EFL Learners - Mukhtar, Hafsa Pir; Zuraina, Ali; Ruhil Amal, Azmuddin (European Publisher, 2023)
This literature review analyzes recent researches on importance of vocabulary knowledge in reading comprehension in learners of English as a foreign language (EFL). Whether learning English as a foreign or second language, vocabulary acquirement is a dominant part, and learners can face difficulties in reading and processing text. EFL learners and instructors know that most of the reading problems that learners face are related to word recall and vocabulary acquisition. Thus, this article is an attempt to increase our knowledge on the importance of vocabulary and its relationship to reading comprehension. The review includes discussion and analysis of twelve published articles in the last decade on the importance of vocabulary knowledge in reading comprehension in the context of learning English as a foreign language. Twelve recent articles have been analyzed on the topic and the most up-to-date information on the subject. This study used content analysis as a data analysis method. The results concluded that vocabulary knowledge is important in reading comprehension or in reading texts in an EFL context; This importance will be considered and discussed in the following article.